Dumped a journey of lessons through breakups, mishaps and misadventures - Amal Nadiah Ghazali 1987- (MPH Group Publishing Sdn Bhd, 2017)
Amal Nadiah Ghazali explores the fascinating tale about a young woman who gets dumped by her boyfriend a day before her birthday. Follow her many adventures in travelling, bad dates, hilarious hiccups and wake-up calls as she pursues the purpose of it all. Through her journey, she recalls lessons on growing up, what love really means, finding her footing in the world, and discovering whether there is more to life than just a good story.